KUPAS TUNTAS AL-BAI’ - Ajuna, Luqmanul Hakiem (Universitas Islam Negeri Sunan Kudus, 2016)
Some people agreed that trade transaction can give greatadvantages to develop the region. The transaction should bedone properly therefore both of the sides get the benefit. It willbe done if we apply the principle of Syari‟ah. Since Islamspread out by the Prophet Muhammad Saw, it is already wellorganized from the process until the detail things. Trade inIslam will be valid if they fulfilled all the requirements andobedient all the pillars. The problem is mostly happened inkhiyar. Most of the people do not understand well what it isand how to apply khiyar itself. They should be already knownabout it before they want to do the transaction. According toHadist of Moslem they are not allowed to enter the market ifthey do not know the rules. By applying Syari‟ah tradetransaction hopefully can give calm and pleasure to everyoneand the most important thing is get bless from Allah SWT.